PERAN PENGALAMAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN: SUATU TINJAUAN TEORITIS DAN EMPIRIS - Muhammad Ilham (Master of Management, Mataram University, 2022)
Work experience is very necessary in improving employee performance in the company. Employee work experience shows the level of mastery of skills. Employees who have had more years of service will have various kinds of work experience in solving various kinds of problems within the company. It is expected that employees will have good quality resources in improving work performance. The purpose of this study is to describe the role of work experience in improving employee performance scientifically based on the results of the existing literature review. If employees have a lot of work experience, then the abilities possessed by employees will be in accordance with the work given, so that employees have high performance. This employee performance refers to the results of work in completing the work. This role has a positive nature which means the more work experience an employee has, the employee's performance will increase. Keywords: Work Experience; Employee Performance; Performance